Case Report: Sequential Development of Three Mature Lymphoid Neoplasms in a Single Patient: Clonal Relationship and Molecular Insights - Salvetti, Chiara; Vitale, Candida; Griggio, Valentina; Drandi, Daniela; Jones, Rebecca; Bonello, Lisa; Bomben, Riccardo; Bragoni, Alberto; Bagnara, Davide; Fais, Franco; Gattei, Valter; Cavallo, Federica; et al. (Frontiers in Oncology, 2022)
Two main variants of Richter sSyndrome (RS) are recognized, namely the dDiffuse Llarge B-cCell lLymphoma (DLBCL) and the Hodgkin’s lLymphoma (HL) variant. Clonal relationship, defined as an identity of the immunoglobulin heavy chain variable (IGHV) region sequence between Cchronic Llymphocytic Lleukemia (CLL) and RS clones, characterizes patients with a poor prognosis. Due to method sensitivity, this categorization is performed without considering the possibility of small-size ancillary clones, sharing the same phenotype with the pre-existing predominant CLL clone, but with different IGHV rearrangements. Here we describe and molecularly profile the peculiar case of a patient with a CLL-likeCD5+ Mmonoclonal B-cCell Llymphocytosis (MBL), who sequentially developed a DLBCL, which occurred concomitantly to progression of MBL to CLL, and a subsequent HL. Based on standard IGHV clonality analysis, DLBCL was considered clonally unrelated to the concomitantly expanded CLL clone and treated as a de novo lymphoma, achieving a persistent response. Three years later, the patient further developed a clonally unrelated HL, refractory to bendamustine, which was successfully treated with brentuximab vedotin and radiotherapy, and later with pembrolizumab. We retrospectively performed additional molecular testing, by applying Next- Generation Sequencing (NGS) of immunoglobulin repertoire (Ig-rep) techniques and a more sensitive allele-specific oligonucleotide-droplet digital PCR (ASO-ddPCR) strategy, in order to quantitatively investigate the presence of the rearranged IGHV genes in tumor specimens collected during the disease course. In this highly complex case, the application of modern and sensitive molecular technologies uncovered that DLBCL, initially considered as a de novo lymphoma, was instead the result of the transformation of a pre-existing ancillary B-cell clone, which was already present at the time of first MBL diagnosis. A similar approach was also applied on HL sample, showing its clonal unrelatedness to the previous MBL and DLBCL.